2016
DOI: 10.1123/japa.2015-0066
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Habitual Levels of Physical Activity According to Impact in Older People: Accelerometry Protocol for the VIBE Study

Abstract: Physical activity (PA) may need to produce high impacts to be osteogenic. The aim of this study was to identify threshold(s) for defining high impact PA for future analyses in the VIBE (Vertical Impact and Bone in the Elderly) study, based on home recordings with triaxial accelerometers. Recordings were obtained from 19 Master Athlete Cohort (MAC; mean 67.6 years) and 15 Hertfordshire Cohort Study (HCS; mean 77.7 years) participants. Data cleaning protocols were developed to exclude artifacts. Accelerations ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 14 publications
2
53
0
Order By: Relevance
“…The people with diabetes' own educational achievement showed an even stronger association with the development of ESRD, there was an approximately five times increase in risk of developing ESRD in those not continuing to university, which was significant also when adjusted for parental education. These results are in accordance with previous studies in which adults with Type 1 diabetes and low SES have been shown to have a higher risk of complications [19,20] and early death [21][22][23]. A Swedish populationbased study by Rawshani et al showed a two-to threefold increase in risk of cardiovascular disease and mortality associated with low SES in people with Type 1 diabetes; both educational level and income level were studied [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The people with diabetes' own educational achievement showed an even stronger association with the development of ESRD, there was an approximately five times increase in risk of developing ESRD in those not continuing to university, which was significant also when adjusted for parental education. These results are in accordance with previous studies in which adults with Type 1 diabetes and low SES have been shown to have a higher risk of complications [19,20] and early death [21][22][23]. A Swedish populationbased study by Rawshani et al showed a two-to threefold increase in risk of cardiovascular disease and mortality associated with low SES in people with Type 1 diabetes; both educational level and income level were studied [24].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in accordance with previous studies in which adults with Type 1 diabetes and low SES have been shown to have a higher risk of complications [19,20] and early death [21][22][23]. As a marker for SES, we used educational level and receipt of social support.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, since acceleration peaks are recorded in time sequence, artefacts and errors can be identified more readily [16]. In the present study, we aimed to use this approach to characterise day-to-day exposure to higher vertical impacts in older individuals, based on four different cohorts of which three were population based, and one recruited on the basis of high PA participation (Master Athlete cohort (MAC)).…”
Section: Introductionmentioning
confidence: 99%
“…Accelerometers had a sampling frequency of 50 Hz. The process of analysing the data retrieved from the accelerometers used a custom code and is described in detail by Deere and colleagues [14]. In summary, the raw data from the accelerometers were imported into Stata 13 (StataCorp, College Station, TX).…”
Section: Methodsmentioning
confidence: 99%